Transcriptomic differences between euryhaline and stenohaline malaria vector sibling species in response to salinity stress. Issue 10 (31st March 2016) - Uyhelji, Hilary A.; Cheng, Changde; Besansky, Nora J.
Abstract: Evolution of osmoregulatory systems is a key factor in the transition of species between fresh‐ and saltwater habitats. Anopheles coluzzii and Anopheles merus are stenohaline and euryhaline malaria vector mosquitoes belonging to a larger group of sibling species, the Anopheles gambiae complex, which radiated in Africa within the last 2 million years. Comparative ecological genomics of these vector species can provide insight into the mechanisms that permitted the rapid radiation of this species complex into habitats of contrasting salinity. Here, we use RNA‐Seq to investigate gene expression differences between An. coluzzii and An. merus after briefly exposing both young and old larval instars of each species to either saltwater (SW) or freshwater (FW). Our study aims to identify candidate genes and pathways responsible for the greater SW tolerance of An. merus . Our results are congruent with the ability of gene induction to mediate salinity tolerance, with both species showing increasing amounts of differential gene expression between SW and FW as salt concentrations increase. Besides ion transporters such as AgAE2 that may serve as effectors for osmoregulation, we also find mitogen‐activated protein kinases that may serve in a phosphorylation signalling pathway responding to salinity, and report potential cross‐talk between the mosquito immune response and osmoregulation. This study provides a key step towards applying the growing molecular knowledge of these malaria vectors to improve understanding of their ecological tolerances and habitat occupancy.